Web Accessibility: a foundation for research - John Karat, Jean Vanderdonckt, Gregory Abowd, Gaëlle Calvary, John Carroll, Gilbert Cockton, Mary Czerwinski, Steve Feiner, Elizabeth Furtado, Kristina Höök, Robert Jacob, Robin Jeffries, Peter Johnson, Kumiyo Nakakoji, Philippe Palanque, Oscar Pastor, Fabio Paternò, Costin Pribeanu, Marilyn Salzman, Chris Schmandt, Markus Stolze, Gerd Szwillus, Manfred Tscheligi, Gerrit van der Veer, Schumin Zhai, Simon Harper, Yeliz Yesilada. (Springer, 2017)
366 p.